Successful management of a cerebral abscess secondary to chronic cholesteatoma caused by Prevotella melaninogenica and Peptococcus anaerobius – A case report and literature review - Carlo Gulì; Luigi Basile; Francesca Graziano; Paola Di Carlo; Domenico Gerardo Iacopino; Antonio Cascio; Rosario Maugeri (Interdisciplinary Neurosurgery, 2016)
Cerebral abscess following cholesteatomatous otomastoiditis is a life-threatening complication and poses diagnostic and therapeutic challenges. We report a case of life-threatening cerebritis and cerebral abscess due to a collection of pus from an aerobic super infections occurring months after the apparent resolution of an otogenic brain abscess in a 67-year-old immunocompetent Italian female. Two gram-positive anaerobic pathogens were isolated during secondary neurosurgical procedures and antibiotic treatment was adopted to resolve the complications. Another objective of this study was to review the literature on gram-positive anaerobic pathogens and brain abscess complications in patients with fistula, and to highlight the importance of short imaging in monitoring treatment during long-term antibiotic therapy for otogenic brain abscess to avoid abscess recurrence. Isolating the strain and monitoring response to treatment with magnetic resonance imaging may improve the prognosis. The study also highlights the need for a close cooperation between infectious disease consultants and neurosurgeons.